From Tetrahedral Tetraphosphonic Acids E[p-C6H4P(O)(OH)2]4 (E=C, Si) to Porous Cu- and Zn-MOFs with Large Surface Areas - Schuetrumpf, Alexandra; Bulut, Aysun; Hermer, Nele; Zorlu, Yunus; Kirpi, Erdogan; Stock, Norbert; Yazaydin, A. Ozgur; Yuecesan, Guendog; Beckmann, Jens (WILEY-V C H VERLAG GMBH, 2017)
This study describes the porous MOFs Cu(2)H(4)STPPA.2 H2O (1.2 H2O), Zn(2)H(4)STPPA (2) and Zn(2)H(4)MTPPA (3) obtained using the tetrahedral linkers tetraphenylmethane tetrakis-4-phosphonic acid (H(8)MTTPA) and tetraphenylsilane tetrakis-4-phosphonic acid (H(8)STPPA) under solvothermal conditions. X-ray structures reveal 3D frameworks with large assessable voids. The percentage void volumes and the specific BET surface areas of 1 (48.7 %, 794 m(2)/g), 2 (48.1 %, 565 m(2)/g) and 3 (51.3 %, 927 m(2)/g) predicted by molecular simulations are among the highest reported for MOFs derived from phosphonic acids.
Keywords: Ligand Design; Metal Organic Solids; MOF; Organophosphonates; METAL-ORGANIC FRAMEWORKS; ADSORPTION; TECTONS; DESIGN; LIGAND; ROUTE; GASES; Chemistry